2018
DOI: 10.1038/s41390-018-0222-6
|View full text |Cite
|
Sign up to set email alerts
|

Adverse neuropsychiatric development following perinatal brain injury: from a preclinical perspective

Abstract: Perinatal brain injury is a leading cause of death and disability in young children. Recent advances in obstetrics, reproductive medicine and neonatal intensive care have resulted in significantly higher survival rates of preterm or sick born neonates, at the price of increased prevalence of neurological, behavioural and psychiatric problems in later life. Therefore, the current focus of experimental research shifts from immediate injury processes to the consequences for brain function in later life. The aetio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 293 publications
(382 reference statements)
0
8
0
1
Order By: Relevance
“…Significant evidence suggests an interactive effect of fetal sex and perinatal neuroinflammation in the pathogenesis of neurodevelopmental disorders, where factors such as the dose of the immunogen, the gestational timing, and acute versus chronic nature of the immune challenge are important [147]. An array of rodent models have been developed to explore the link between altered neural-immune interactions and ASD and/or other neurodevelopmental disorders.…”
Section: Animal Models Of Perinatal Inflammation: Behavioral Abnormentioning
confidence: 99%
“…Significant evidence suggests an interactive effect of fetal sex and perinatal neuroinflammation in the pathogenesis of neurodevelopmental disorders, where factors such as the dose of the immunogen, the gestational timing, and acute versus chronic nature of the immune challenge are important [147]. An array of rodent models have been developed to explore the link between altered neural-immune interactions and ASD and/or other neurodevelopmental disorders.…”
Section: Animal Models Of Perinatal Inflammation: Behavioral Abnormentioning
confidence: 99%
“…This study examined the electrophysiological responses to emotional (fearful and happy) prosody in neonates with and without clinically diagnosed brain injury during the first days following birth (0–10 days), and explored the associations between early ERP signatures in neonates and later neurodevelopment at 30 months of age. As perinatal brain injury is associated with adverse long-term sequelae including cognitive and neuropsychiatric disorders (42) and that the processing of emotion information is a critical social cognition during development, we hypothesized that while healthy neonates could process and show differential MMRs to specific emotions, neonates with brain injuries would exhibit deficits in emotion processing and have altered MMRs compared to healthy controls. Moreover, we aimed to study if any identified early alterations in impaired emotion processing were predictive of cognitive development in later childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Microdialysis studies may therefore extend these initial findings by investigating the exact role of dopamine in distinct brain areas. Given that rodent models have demonstrated cognitive dysfunctions due to aberrant dopaminergic signaling in the medial prefrontal cortex (Castner et al 2004), future studies may also address this issue by analyzing whether immunosuppressive compounds affect working memory in tests such as the radial maze, the Barnes maze, or the Morris water maze (Bendix et al 2019).…”
Section: Discussionmentioning
confidence: 99%